Pelatihan Paralegal sebagai Strategi Penguatan Etika, Jejaring, dan Kemitraan di Desa Bubalango, Kec. Sumalata - Muslim A. Kasim; Nurwita Ismail (Lembaga Pengembangan Kinerja Dosen, 2025)
Paralegals play a crucial role in providing access to justice, particularly in legal aid provision and legal empowerment for communities. In this context, the role of paralegals is essential in bridging the gap in legal access, especially in areas that lack sufficient numbers of advocates. Bubalango Village in Sumalata District, North Gorontalo Regency, faces limitations in access to information and legal understanding, which hinders the community from obtaining the legal assistance they need. Therefore, the Faculty of Law at the University of Gorontalo organized a paralegal training program to enhance the community’s capacity in providing basic legal aid, educating citizens about their rights, and strengthening networking and partnerships with legal institutions and the government. The training includes topics on the Indonesian legal system, citizens' rights, paralegal ethics, and practical skills in drafting legal documents and mediation. It is hoped that this training will strengthen access to justice and build a more inclusive legal system at the village level